Bodyweight BOSU ball exercises - Snarr, R. L.; Wirbiezcas, M.; Colbert, A.; Langford, E.; Hogan, G. (Strength and Conditioning Journal, 2021)
A growing trend in strength and conditioning is the execution of traditional exercises on instability devices. With the addition of these implements, there is a greater challenge to maintain stability and balance. Implementing a device, such as the BOSU ball, may provide benefits to individuals rehabilitating from an injury, older individuals, and those looking to increase overall health benefits. Thus, this column provides detailed descriptions of the proper technique, advanced progressions, and exercise prescription for 4 bodyweight BOSU ball exercises.